EVALUATING THE AIRTIGHTNESS OF RESIDENTIAL BUILDINGS BY USING PREDICTIVE MODELS (Advances in Civil and Architectural Engineering, 2021)
A building’s energy consumption can be greatly reduced by improving its airtightness. Thus, when designing new and retrofitting existing buildings, it is important to accurately calculate energy losses caused by uncontrolled air leakage. A building’s airtightness can be measured by a pressurization test but only at the final stage of construction, and for large buildings this procedure can be very expensive and often produces results of questionable quality. Another way to evaluate airtightness is by using predictive models. In this study, we compare three predictive models for determining airtightness, using an airtightness database from buildings in the city of Osijek and in a suburban area. Using these models, we calculated airtightness values for 20 buildings and compared these predictions with measured results.